The process of pedagogical image development - Stonoha, A. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the process of developing pedagogical image and proves that the process of image cultivation is aimed at creating a certain image of an object from the audience’s point of view. Development of the teacher's image can be carried out in two different ways: spontaneously and purposefully. Every teacher has an image regardless of his/her personal views on this topic. It is revealed that the process of constructing an image takes place as a result of actions directly aimed at forming the impression of the teacher about him/herself, and as a result of the whole system of professional activity and communication. The author analyses the image of the teacher from two positions: as a stereotype, in the case of talking about the image of the profession, and as an appearance – if it is a personal image. The notion of the image of the teacher in the broad sense is an emotionally coloured stereotype of the perception of the teacher's image in the minds of students, colleagues, social environment, in the mass consciousness, or, in the narrow sense, is the image of one teacher in whose consciousness there is a choice of a certain manner of behaviour expressed in an individual style of activity. The author regards the image creation as the process which is characterised by subject-object relationships, and states that the image of the teacher is formed under the influence of many factors. It is proved that the development of the teacher's image begins when he/she studies at a professional institution when, as a student, the future teacher acquires a system of professional and general knowledge, skills and abilities, and faces the solution of emerging problems during the pedagogical practice at educational institutions when he/she perceives some samples of teachers’ images.